Spiritual Quotient Development: Pengajian Kitab Kuning pada Anak - Alfayyadl, Ahmad Fasya (Journal of Islamic Education Counseling, 2022)
Children who are state assets in the future must be protected both physically and mentally. This is developed through the potential for intelligence in children, namely intellectual, emotional, and spiritual. However, spiritual intelligence is the highest intelligence, because it can function intellectual intelligence and emotional intelligence. This research was conducted using qualitative methods with descriptive analysis. The approach used is a case study because the researcher analyzes cases that occurred in a pesantren in Cirebon. Data collection techniques used are interviews, observation, and documentation. This article aims to develop children's spiritual intelligence, the effort that is done is through the recitation of the yellow book. At the Daar El Amanah Islamic Boarding School, children of their primary school age learn about monotheism and worship. The results of the research conducted indicate the development of spiritual intelligence in children through the recitation of the yellow book. Because they gain new knowledge and understanding. This development is felt by parents who always pay attention to the activities of their children, because children are more able to interpret the life they face and can distinguish between good and bad things.